Let's have a look at this supposedly simple relation: $$ \begin{cases} f(n)=2\cdot f(n-1)+n \\ f(1)=1 \end{cases} $$

After a few expansions, for $n=5$, we get

$$ \begin{align} f(5)&=2(2(2(2f(1)+2)+3)+4)+5) \\ &=2^4f(1)+\sum_{i=0}^{3}{2^i\cdot (5-i)} \end{align} $$

So, we can generalize to $$ f(n)=2^{n-1}+\sum_{i=0}^{n-2}{2^i\cdot (n-i)} $$

After that, I still couldn't arrive at the final solution, without any sum terms.

So, using only elementary tools (i.e without generating functions, etc.), how can one solve this relation?

  • 1
    $\begingroup$ Hint: Compare it to $2^{n+1}$. $\endgroup$ – lulu Sep 17 at 19:09

Looking at homogenous equation $f(n) = 2f(n-1)$, we get $f(n) = A \cdot 2^n$ for some constant $A \in \mathbb R$ is our general solution to that equation.

Now we want to find one solution to equation $f(n) = 2f(n-1) + n$.

Looking at the remaining $n$, we can guess it should be some sort of linear, so let's try $f_*(n) = an+b$, where by $f_*$ I denote special solution.

Then we have $an + b = 2a(n-1) + 2b + n$ which is equivalent to: $n(a+1) + b -2a = 0$

It must holds for any $n \in \mathbb N$, so we need $(a+1) = 0$, that means $a=-1$ and $b-2a = 0$, so $b = 2a = -2$

So our special solution is $f_*(n) = -n-2$.

Now, any solution to our system of equation is of the form : general solution + special solution.

So plugging it in, we have our solution to be $f(n) = A\cdot 2^n -n - 2$.

Plugging $f(1) = 1$, to get the value of $A$, we have:

$1 = 2A - 1 - 2$, so $A=2$

And our solution is $f(n) = 2^{n+1} - n - 2$


$$ \begin{align} f(n)&=2f(n-1)+n\tag1\\ f(n)+(n+2)&=2(f(n-1)+(n+1))\tag2\\ g(n)&=2g(n-1)\tag3 \end{align} $$ Explanation:
$(1)$: original recursion
$(2)$: add $n+2$ to both sides
$(3)$: let $g(n)=f(n)+(n+2)$

Starting with $g(1)=f(1)+3=4$, we get $$ g(n)=2^{n+1}\tag4 $$ and therefore, $$ f(n)=2^{n+1}-n-2\tag5 $$

  • $\begingroup$ Probably, this is the simplest solution. Simpler then mine. $\endgroup$ – Alexandre Frias Sep 17 at 19:29
  • 1
    $\begingroup$ @AlexandreFrias: The $\sum_{n=2}^m\frac{n}{2^n}$ is nice and mechanical, but a bit daunting to encounter. I looked at this by applying the shift operator on sequences, $S$, and got $(S-2)f(n)=n+1$ and so $(S-1)^2(S-2)f(n)=0$ which turns this into a homogeneous third degree linear difference equation whose solution is of the form $f(n)=A2^n+Bn+C$. Commuting the difference equation to $(S-2)(S-1)^2f(n)=0$ gave $(S-2)(f(n)+n+2)=0$, which is where I got $g(n)=f(n)+n+2$. $\endgroup$ – robjohn Sep 17 at 19:53

Divide both parts by $2^n$ and you have a linear recurrence



This is a telescopic term then you can apply the summation in both parts





We try to write $f(n)=g(n)+h(n)$ where$$g(n)-2g(n-1)=n$$$$h(n)-2h(n-1)=0$$

Now $h(n)$ is easy with $h(n)=2^nh(0)$ - but we don't know what $h(0)$ is yet.

For forms like this with a polynomial in $n$ on the right-hand side, we try a solution with $g(n)$ being a polynomial of the same degree [there are special cases where a higher degree is necessary].

So here we want $g(n)=an+b$ to be linear.

We call $g(n)$ a particular solution, and $h(n)$ a solution of the "homogeneous part".

That should be enough clue for you to try to finish it yourself.

Note: Generally the unknowns in the particular solution will be determined direct from the recurrence, while those in the homogeneous part (which represents the degrees of freedom in the solution) will be found by reference to the initial conditions.


Your recurrence relation is linear, but not homogeneous.

One approach is as follows: begin by solving the homogeneous recurrence relation, $$ f(n) = 2 f(n - 1). $$ We end up with a general solution of $f_H(n) = C2^n$. Now, it suffices to find one "particular solution" to the original non-homogeneous difference equation. Following the method of undetermined coefficients, we take the ansatz $$ f(n) = an + b \implies\\ f(n-1) = an + (b-a). $$ Plugging this in to our recurrence relation yields $$ f(n) = 2 f(n - 1) + n \implies an + b = 2[an + (b-a)] + n\implies\\ an + b = (2a+1)n + 2b-2a \implies\\ (a + 1)n + (2a-b)= 0 $$ So, $a = -1$, $b = -2$ will work. We can therefore take $ f_P(n) = -n-2. $ Thus, our general solution is $$ f(n) = f_H + f_P = C \,2^n - n - 2. $$ Using the initial conditions, solve for $C$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.